All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 27596 by abdo imad last updated on 10/Jan/18
find∫3x2−x3dx
Commented by abdo imad last updated on 28/Jan/18
I=∫3x3(1x−1)dx=∫x1x−1dxletusethech.1x−1=t⇒1x−1=t2⇒1x=1+t2⇒x=11+t2I=∫11+t2t.−2t(1+t2)2dt=−2∫t2(1+t2)3dt=−2∫1+t2−1(1+t2)3dt=−2∫dt(1+t2)2+2∫dt(1+t2)3butthech.t=tanθgiveI=−2∫1+tan2θ(1+tan2θ)2dθ+2∫1+tan2θ(1+tan2θ)3dθ=−2∫dθ1+tan2θ+2∫dθ(1+tan2θ)2=−2∫cos2θdθ+2∫cos4θdθbutwehave∫cos2θdθ=∫1+cos(2θ)2dθ=12θ+14sin(2θ)∫cos4θdθ=∫(1+cos(2θ)2)2dθ=14∫(1+2cos(2θ)+1+cos(4θ)2)dθ=14θ+14sin(2θ)+18θ+132sin(4θ)=38θ+14sin(2θ)+132sin(4θ)soI=−θ−12sin(2θ)+34θ+12sin(2θ)+116sin(4θ)I=−14θ+116sin(4θ)withθ=arctan(1x−1).
Terms of Service
Privacy Policy
Contact: info@tinkutara.com